2015
DOI: 10.12688/f1000research.5686.2
|View full text |Cite
|
Sign up to set email alerts
|

An Open Science Peer Review Oath

Abstract: One of the foundations of the scientific method is to be able to reproduce experiments and corroborate the results of research that has been done before. However, with the increasing complexities of new technologies and techniques, coupled with the specialisation of experiments, reproducing research findings has become a growing challenge. Clearly, scientific methods must be conveyed succinctly, and with clarity and rigour, in order for research to be reproducible. Here, we propose steps to help increase the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…General guidelines from the open science framework (OSF) could be used to improve the reliability, reproducibility, and generalizability of studies in this field of environmental and educational psychology (Munafò et al, 2017). We have covered design and analysis above, but other cultural practices could be adopted, such as pre-registration (van't Veer and Giner-Sorolla, 2016), reporting of null results and more transparency in the sharing of data and the analytical workflow.…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…General guidelines from the open science framework (OSF) could be used to improve the reliability, reproducibility, and generalizability of studies in this field of environmental and educational psychology (Munafò et al, 2017). We have covered design and analysis above, but other cultural practices could be adopted, such as pre-registration (van't Veer and Giner-Sorolla, 2016), reporting of null results and more transparency in the sharing of data and the analytical workflow.…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…The core principles of UPSIDE highlight the public availability of data and materials [ 19 ]. Nosek et al [ 20 ] broadly suggested the use of checklists by authors, reviewers and editors to help assess the overall quality of manuscripts, and Aleksic et al [ 21 ] offer a general ‘open science peer reviewer's oath’ that suggests general principles for reviewers to help improve the status quo. The journal Nature Genetics has specified that all articles submitted must make available materials to reviewers and future readers, via permanent, public repositories [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach was picked up by other countries, including the United States of America through the National Science Foundation's Office of Cyber-Infrastructure [17] and The Netherlands through The Netherlands e-Science Center 1 . Although e-Science is funded differently across the world, it represents a paradigm shift, identifying the need for infrastructure and tools to support data-intensive research workflows, supporting the case for open data and open science to make research more efficient, and supporting research integrity as experiments become more complex.…”
Section: An Ambitious Planmentioning
confidence: 99%
“…Over the last 8 years, it has evolved (with funding from the Engineering and Physical Sciences Research Council, Economic and Social Sciences Research Council, and Biotechnology and Biological Sciences Research Council) to bring the community together in tackling these problems. It works on several scales, providing consultancy and advice direct to researchers who are developing software, enabling researchers across the UK to access appropriate training, and running events and campaigns to support and facilitate champions of research culture change through best practice [23] and policy [1].…”
Section: Building a Cross-disciplinary Communitymentioning
confidence: 99%